Correction of serum chloride concentration in dogs with congestive heart failure. (11th December 2020) - Adin, Darcy; Atkins, Clarke; Londoño, Leonel; Del Nero, Bruna
Abstract: Background: Hypochloremia associated with congestive heart failure (CHF) in dogs is likely multifactorial. Loop diuretics cause 1:2 sodium [Na + ]:chloride [Cl − ] loss, whereas water retention causes a 1:1 [Na + ]:[Cl − ] dilution. Mathematical [Cl − ] correction separates these effects on [Cl − ]. Hypothesis: We hypothesized that corrected [Cl − ] (c[Cl − ]) would not differ from measured [Cl − ] (m[Cl − ]) in dogs with controlled CHF because of loop diuretics, and dogs with refractory CHF would have higher c[Cl − ] than m[Cl − ], indicating relative water excess. Animals: Seventy‐one client‐owned dogs with acquired heart disease, without CHF (NO‐CHF), 76 with Stage C CHF and 24 with Stage D CHF. Methods: Clinicopathological data from a previous study were retrospectively analyzed. Corrected [Cl − ], m[Cl − ], and differences were compared among NO‐CHF, Stage C CHF, and Stage D CHF, using the formula: c[Cl − ] = (mid‐reference range [Na + ]/measured [Na + ]) × m[Cl − ]. Results: Corrected [Cl − ] and m[Cl − ] were lower in Stage D vs Stage C and NO‐CHF (all P < .0001). The c[Cl − ] was higher than m[Cl − ] in Stage D ( P < .0001) but not Stage C or NO‐CHF. Median difference between c[Cl − ] and m[Cl − ] was higher for Stage D vs Stage C ( P = .0003). No hypochloremic Stage D dogs had normal c[Cl − ], but 11/24 had [Cl − ] that was increased by >2 mmol/L. Conclusions and Clinical Importance: Serum [Cl − ] increased after mathematical correction in Stage D CHF dogs but not in Stage C and NO‐CHF dogs. Although c[Cl − ] was higher than m[Cl − ] in Stage D dogs supportive of relative water excess, hypochloremia persisted, consistent with concurrent loop diuretic effects on electrolytes. Future study correlating c[Cl − ] to antidiuretic hormone concentrations is warranted.